The greater the contrast, the greater the potential: On the effects of focus in syntax. Issue 1 (18th January 2021) - Cruschina, Silvio
The most debated syntactic reflex that is typically associated with contrast is the movement of a contrastive constituent to a dedicated, left-peripheral position. For Italian and Spanish, it has been claimed that focus fronting (FF) must be sanctioned by a contrastive interpretation of the focus, while non-contrastive focus generally occurs postverbally (see, e.g., Rizzi 1997 ;Zubizarreta 1998 ;Belletti 2004 ;López 2009 ). Only sentences with a postverbal focus are thus judged as pragmatically felicitous answers to the corresponding wh-questions. Some scholars, however, have recently reported different views and data, showing that non-contrastive preverbal foci are indeed accepted by native speakers in answers to wh-questions. In this paper, I argue that a solution to this problem can be found if the binary distinction between contrastive and non-contrastive focus is abandoned, and different 'degrees' or 'types' of contrastive focus are identified, depending on the way the set of alternatives is pragmatically exploited (Krifka 2007 ;Cruschina 2012 ). I show that languages are syntactically sensitive to specific types of focus with which special operations (e.g. FF) associate. Following Bianchi, Bocci & Cruschina (2015 ;2016 ), I then argue that FF is in fact triggered not by contrast per se, but by the conventional implicature that is associated with a specific type of focus.